Perbandingan Kemampuan Beban Pajak Tangguhan dan Penyisihan Aktiva Pajak Tangguhan Entitas dalam Mendeteksi Manajemen Laba - , YOSHUA GEDY ANDREA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to examine deferred tax expense and deferred tax asset valuation allowance influence as an instrument of earnings management to avoid losses, where there is two scenarios of earnings target, to avoid earnings decrease and to avoid loss. The population of this research is the manufacturing firms listed on the Indonesia Stock Exchange in the year 2007 â 2010. There were 130 firm-yaers obrservation for earnings target to avoid earnings decrease scenario and 99 firmyears for earnings target to avoid loss. The sample selection was done by purposive sampling method. The results showed that deferred tax expense affect significantly in detecting earnings management only for earnings target to avoid earnings decrease. Deferred tax asset valuation allowance variable didnât affect significantly in detecting earnings management for both earnings target